Functional neuroanatomy of body checking in people with anorexia nervosa. Issue 7 (6th June 2013) - Suda, Masashi; Brooks, Samantha J.; Giampietro, Vincent; Friederich, Hans‐Christoph; Uher, Rudolf; Brammer, Michael J.; Williams, Steven C.R.; Campbell, Iain C.; Treasure, Janet
ABSTRACT Objective The neural correlates of body checking perceptions in eating disorders have not yet been identified. This functional Magnetic Resonance Imaging study examined the neuroanatomy involved in altered perception and identification with body checking in female with anorexia nervosa (AN). Method Brain activation while viewing images depicting normal weight individuals involved in either body checking behavior or a neutral (noneating disorder) body action, was compared between 20 females with AN and 15 matched healthy controls (HC). Results Females with AN reported higher anxiety compared to HC during the body checking task. The level of anxiety positively correlated with body shape concern scores. People with AN had less activation in the medial prefrontal cortex (PFC) and right fusiform gyrus compared to HC in response to body checking compared to neutral action images. Body shape concern scores correlated negatively with medial PFC activation in AN group. Discussion This preliminary study with modest power suggests that AN patients have reduced activation in cortical areas associated with self‐reference, body action perception, and social cognition in females with AN. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:653–662)